Navigating the challenges of the COVID-19 outbreak: Perspectives from the radiation oncology service in Singapore. (July 2020) - Tey, Jeremy; Ho, Shaun; Choo, Bok Ai; Ho, Francis; Yap, Swee Peng; Tuan, Jeffrey K.L.; Leong, Cheng Nang; Cheo, Timothy; Sommat, Kiattisa; Wang, Michael L.C.
Highlights: Unique considerations for radiation department operating during Covid-19 outbreak. Highlights the challenges of radiation departments providing care during a pandemic in Singapore. Highlights practical steps on handling oncology patients during infectious outbreak. Abstract: In December 2019, pneumonia of unknown cause was reported by China to WHO. The outbreak was found to be caused by a coronavirus which was officially named "severe acute respiratory syndrome coronavirus 2" (SARS-CoV-2), and the disease caused by it was named 'COVID-19'. The first case in Singapore was confirmed on 23rd January 2020. With lessons learnt from the SARS epidemic in 2003 and the H1N1 flu pandemic in 2009, Singapore was much better prepared to deal with the virus outbreak. The government has taken swift measures to contain and break the chain of transmission. Healthcare workers face the challenge of keeping patients and staff safe from the disease. There is a higher risk of mortality of COVID-19 in cancer patients and hence unique considerations for a radiation oncology department operating in an infectious disease outbreak. This article is the recommendations and adapted workflow from the two National Cancer Centres in Singapore with the endorsement by the working committee of the Chapter of Radiation Oncology, Academy of Medicine, Singapore. It highlights the challenges that radiation oncology departments in Singapore face and the appropriate recommended responses. This includes interventions, business continuity plans and workflow in managing a COVID-19 positive patient on radiotherapy.